2011
DOI: 10.1371/journal.pone.0016959
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Treatment of Mice Infected with Trypanosoma cruzi and Implications for the Pathogenesis of Chagas Disease

Abstract: Chagas disease, caused by infection with Trypanosoma cruzi, is an important cause of cardiovascular disease. It is increasingly clear that parasite-derived prostaglandins potently modulate host response and disease progression. Here, we report that treatment of experimental T. cruzi infection (Brazil strain) beginning 5 days post infection (dpi) with aspirin (ASA) increased mortality (2-fold) and parasitemia (12-fold). However, there were no differences regarding histopathology or cardiac structure or function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 45 publications
3
63
0
3
Order By: Relevance
“…The suppressor of cytokine signaling (SOCS) family plays an important role in immune responses by modulating cytokine signaling pathways, and AhR has been shown to modulate SOCS2 expression in the mouse model of T. gondii infection (46). SOCS2 is also induced during T. cruzi infection (52) and was shown to be modulated as a result of aspirin treatment (53). Therefore, we examined SOCS1, -2, and -3 expression in the brain tissue of infected mice.…”
Section: Ahr Deficiency Results In Increased Parasitemia and Mortalitmentioning
confidence: 99%
“…The suppressor of cytokine signaling (SOCS) family plays an important role in immune responses by modulating cytokine signaling pathways, and AhR has been shown to modulate SOCS2 expression in the mouse model of T. gondii infection (46). SOCS2 is also induced during T. cruzi infection (52) and was shown to be modulated as a result of aspirin treatment (53). Therefore, we examined SOCS1, -2, and -3 expression in the brain tissue of infected mice.…”
Section: Ahr Deficiency Results In Increased Parasitemia and Mortalitmentioning
confidence: 99%
“…Previous studies have shown that the release of eicosanoids during infection with T. cruzi regulates host responses and controls disease progression (10,(27)(28)(29)(30)(31). PGs, together with NO and TNF-␣, participate in a complex circuit that controls lymphoproliferative and cytokine responses in T. cruzi infection (28).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies by Ashton et al have suggested that TXA 2 is an important parasite-derived eicosanoid that contributes to parasite proliferation and hence the inflammatory response (28). Several studies also suggest that eicosanoids, in conjunction with cytokines, chemokines, and other inflammatory mediators, are essential for the progression and perpetuation of the chronic phase of the disease (9,29). Since PLA 2 is critical for arachidonic acid release and eicosanoid production, it could con- tribute to the pathogenesis of Chagas' disease via the formation of these mediators.…”
Section: Discussionmentioning
confidence: 99%
“…A key pathological feature of Chagas' disease is inflammation, which is regulated by several mediators, including adhesion molecules, cytokines, eicosanoids, and nitric oxide (6)(7)(8). In the acute stage, these molecules are seen to be important for the development of host resistance, as well as regulating progression to the chronic stages of the disease (9). However, much remains unknown about the host-parasite interactions that contribute to Chagas' disease via these mediators.…”
mentioning
confidence: 99%